Maternal malnutrition and anaemia in India: dysregulations leading to the ‘thin-fat’ phenotype in newborns - Pandit, Prachi; Galande, Sanjeev; Iris, François (Journal of nutritional science (Cambridge), 2021)
Maternal and child malnutrition and anaemia remain the leading factors for health loss in India. Low birth weight (LBW) offspring of women suffering from chronic malnutrition and anaemia often exhibit insulin resistance and infantile stunting and wasting, together with increased risk of developing cardiometabolic disorders in adulthood. The resulting self-perpetuating and highly multifactorial disease burden cannot be remedied through uniform dietary recommendations alone. To inform approaches likely to alleviate this disease burden, we implemented a systems-analytical approach that had already proven its efficacy in multiple published studies. We utilised previously published qualitative and quantitative analytical results of rural and urban field studies addressing maternal and infantile metabolic and nutritional parameters to precisely define the range of pathological phenotypes encountered and their individual biological characteristics. These characteristics were then integrated, via extensive literature searches, into metabolic and physiological mechanisms to identify the maternal and foetal metabolic dysregulations most likely to underpin the ‘thin-fat’ phenotype in LBW infants and its associated pathological consequences. Our analyses reveal hitherto poorly understood maternal nutrition-dependent mechanisms most likely to promote and sustain the self-perpetuating high disease burden, especially in the Indian population. This work suggests that it most probably is the metabolic consequence of ‘ill-nutrition’ – the recent and rapid dietary shifts to high salt, high saturated fats and high sugar but low micronutrient diets – over an adaptation to ‘thrifty metabolism’ which must be addressed in interventions aiming to significantly alleviate the leading risk factors for health deterioration in India.